PENGARUH EKSTRAK DAUN KELOR (Moringa oleifera L.) TERHADAP KADAR GLUKOSA DARAH POST-PRANDIAL Studi Eksperimental pada Tikus Putih Jantan Galur Wistar Model Diabetes Melitus Tipe 2 dengan Induksi Streptozotocin-Nicotinamide - Cyntia Amalia Tyana; Hadi Sarosa (PT. Hasba Edukasi Mandiri, 2026)
Type 2 Diabetes Mellitus (T2DM) is characterized by impaired glucose homeostasis, particularly spikes in 2-hour postprandial blood glucose (2h-PPBG) levels, which often lead to cardiovascular complications. Moringa oleifera L. leaves are known to contain active compounds such as flavonoids and tannins that have the potential to reduce oxidative stress. This study aims to evaluate the effect of Moringa leaf extract on 2h-PPBG levels in T2DM rat models. This experimental study, utilizing a post test only controlled group design, used 24 male Wistar rats randomly allocated into four groups: normal control (NC), negative control (C-), positive control (C+; glimepiride), and treatment (T1; Moringa leaf extract at a dose of 450 mg/kg body weight). The T2DM condition was induced using streptozotocin-nicotinamide (STZ-NA). Blood glucose levels were measured using the GOD-PAP enzymatic colorimetric method. Data on the difference in 2h-PPBG elevation were analyzed using the Kruskal-Wallis test. The mean difference in 2h-PPBG levels in the T1 group (11.19 ± 0.74 mg/dL) was numerically higher than in the C+ (11.06 ± 0.61 mg/dL), C- (10.75 ± 0.39 mg/dL), and NC (10.88 ± 0.37 mg/dL) groups. However, statistical analysis showed no significant difference among all treatment groups (p = 0.604). The administration of Moringa leaf extract at a dose of 450 mg/kg body weight exhibited a stabilizing effect on 2h-PPBG levels comparable to glimepiride, although it did not demonstrate a statistically significant difference in reducing 2h-PPBG levels across the groups.